2015
DOI: 10.1007/s10488-015-0694-1
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of a Change Agent on Use of Evidence-Based Mental Health Practices

Abstract: Children’s service systems are faced with a critical need to disseminate evidence-based mental health interventions. Despite the proliferation of comprehensive implementation models, little is known about the key active processes in effective implementation strategies. This proof of concept study focused on the effect of change agent interactions as conceptualized by Rogers’ diffusion of innovation theory on providers’ (N = 57) use of a behavioral intervention in a child welfare agency. An experimental design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 54 publications
1
16
0
1
Order By: Relevance
“…The ZIP analysis provides estimates of both amount of use, from the Poisson portion of the model, and zero inflation to model an excess of zeros in the data (i.e., no use of the intervention reported for the past 30 days). In these analyses, placement in the enhanced change agent interaction group significantly predicted greater use, as reported in a previous publication (Leathers et al, 2016). However, coefficients for overall attitudes were not significantly associated with intervention use in either part of the ZIP model (Table 2).…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The ZIP analysis provides estimates of both amount of use, from the Poisson portion of the model, and zero inflation to model an excess of zeros in the data (i.e., no use of the intervention reported for the past 30 days). In these analyses, placement in the enhanced change agent interaction group significantly predicted greater use, as reported in a previous publication (Leathers et al, 2016). However, coefficients for overall attitudes were not significantly associated with intervention use in either part of the ZIP model (Table 2).…”
Section: Resultssupporting
confidence: 71%
“…A full description of the study’s methods is found in a previous publication (Leathers, Spielfogel, Blakey, Christian, & Atkins, 2016). Briefly, 57 caseworkers and therapists (“providers”) from a single large urban child welfare agency in the United States were randomly assigned to one of two training conditions, a “training as usual” control group ( n = 26) that received only training and experimental group ( n = 31) that received training enhanced by support after the training.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Without widespread belief (norms and attitudes) that a particular mental health condition warrants attention and that an identified intervention can successfully improve the condition, uptake is unlikely. 16,22 Resources including dedicated staff time and access to ongoing consultation and/or coaching are critical to implementation and sustainment of evidence-based practices 20,23,24 and persuasive change agents have been shown to be central to the adoption of new innovations in community-settings 23,25 Finally, an organization's structure and processes can significantly influence implementation in community mental health settings. 21 To address the need for schoolfocused implementation research and further our understanding of the factors that drive and impede the use of evidence-based practices in schoolsettings, this study expands the use of Mendel's model to examine the implementation of a group-based trauma intervention, the Cognitive Behavioral Intervention for Trauma in Schools (CBITS) in the unique service setting of schools.…”
Section: Discussionmentioning
confidence: 99%
“…Onsite leadership from either the clinician and/or school administrator can strongly influence the use of CBITS on campus. Active onsite leadership has been critical to the implementation of evidence-based practices (EBPs) in other child-service settings 23,25 Additionally, the Reflective Learning Group supervision approach provided by the centralized mental health unit in the Western region was a significant source of support for clinicians. This mirrors earlier studies demonstrating that ongoing implementation support and consultation are crucial to establishing new EBPs within community settings.…”
Section: Change Agentmentioning
confidence: 99%